2020
DOI: 10.3390/ijerph17072434
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring Food Insecurity Using the Food Abundance Index: Implications for Economic, Health and Social Well-Being

Abstract: High levels of food insecurity signal the presence of disparities and inequities in local food access, which have been shown to negatively impact the health and well-being of individuals and communities. However, the approaches used to define and measure high food insecurity, also known as a “food desert”, vary widely across research study and intervention methodology. This paper describes the development and validation of a measurement tool called the “Food Abundance Index” (FAI) which is a scorecard for asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Despite these challenges, policymakers can collaborate with local businesses, community leaders, and public health professionals to devise strategies that increase access to food for older adults. Because this study found variation in magnitude and significance for low access to food with older adult mortality from COVID-19 based on geographic location, a practical public health intervention may involve using the Food Abundance Index (FAI) to measure the level of food insecurity within a geographic region ( Murrell & Jones, 2020 ). The FAI scorecard evaluates (a) access, (b) diversity, (c) quality, (d) density, and (e) affordability using a point system.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Despite these challenges, policymakers can collaborate with local businesses, community leaders, and public health professionals to devise strategies that increase access to food for older adults. Because this study found variation in magnitude and significance for low access to food with older adult mortality from COVID-19 based on geographic location, a practical public health intervention may involve using the Food Abundance Index (FAI) to measure the level of food insecurity within a geographic region ( Murrell & Jones, 2020 ). The FAI scorecard evaluates (a) access, (b) diversity, (c) quality, (d) density, and (e) affordability using a point system.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…However, this is an important access consideration for some populations, like those residing in colonias on the US-Mexico border and in low-income communities in Jamaica [ 30 , 88 ]. For FI, transportation and time to markets may be important among households that do not engage in subsistence farming, e.g., in areas with food scarcity in the USA [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still necessary to develop new effective solutions, whose introduction should be preceded by research on their acceptance amongst older people. Further research is also needed to help bridge the gap between academics, policymakers and practitioners in the area of food security [ 89 ].…”
Section: Discussionmentioning
confidence: 99%